An in Vitro Assay Reveals the Anti-Aging Properties of Temulawak Extract (Curcuma xanthorrhiza L.) - Wargasetia, Teresa Liliana; Widowati, Wahyu; Muthmainnah, Anis Syabani; , Rizal (Folia Medica Indonesiana, 2023)
Highlights: 1. This study investigated the potential of temulawak extract as a cost-effective option for cosmeceutical applications in the treatment of aging. 2. Temulawak extract was found to have the ability to inhibit elastase, hyaluronidase, and tyrosinase activities, thus making it a suitable option for cosmeceutical applications. Abstract Aging is the gradual loss of a tissue's capacity to heal and maintain normal or physiological form and function. Elastase, hyaluronidase, and tyrosinase are the enzymes that contribute to the process of skin aging. The anti-aging effect is connected to the inhibition of these enzymes' activities. Numerous medicinal plants with active metabolites have been extensively utilized to treat aging. The active compounds of temulawak (Curcuma xanthorrhiza L.), such as phenolics, curcuminoids, and xanthorrhizol, have promising properties that may be used as anti-aging agents. This study aimed to determine whether temulawak extract, a potential option for cosmeceuticals, has anti-aging properties that can inhibit the enzymes elastase, hyaluronidase, and tyrosinase. A stock solution was made by dissolving 20 mg of temulawak extract in 1 mL of 100% dimethyl sulfoxide (DMSO). The stock solution was then diluted to produce working solutions with concentrations ranging from 31.25 to 1000"‰Î¼g/mL. An in vitro assay was carried out in three replications to examine the anti-aging activity of the temulawak extract. The in vitro assay investigated the inhibition of the enzyme elastase, hyaluronidase, and tyrosinase at seven different concentrations, with the following ranges: 2.08–66.67 Î¼g/mL for the anti-elastase, 5.21–166.67 Î¼g/mL for the anti-hyaluronidase, and 3.125–100 Î¼g/mL for the anti-tyrosinase. IBM SPSS Statistics for Windows, version 20.0 (IBM Corp., Armonk, N.Y., USA) was used to perform the statistical analysis, with a significance level of"¯p<0.05. Temulawak extract exhibited the highest inhibition rates, reaching 82.72%, 89.41%, and 94.17% for the anti-tyrosinase, anti-elastase, and anti-hyaluronidase activities, respectively. The median inhibitory concentrations (IC50) were 10.66, 70.39, and 55.87 Î¼g/mL for the elastase, hyaluronidase, and tyrosinase activities, respectively. This study revealed that temulawak extract has strong anti-aging properties as it effectively inhibits the activities of elastase, tyrosinase, and hyaluronidase. In conclusion, temulawak extract can be considered a promising candidate for cosmeceutical applications.